2012
DOI: 10.1017/s0317167100015584
|View full text |Cite
|
Sign up to set email alerts
|

Deficiencies in Concussion Education in Canadian Medical Schools

Abstract: Concussion is currently an important public health issue in Canada. There are concerns about the knowledge-base of those involved with the diagnosis and management of concussions. Previous studies have identified deficiencies in the knowledge of concussion of coaches, athletic trainers and the general public.1-3 The present research focuses on the concussion education of medical students because physicians play a critical role in concussion diagnosis and management, including guidelines for return to play, wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 9 publications
1
30
0
Order By: Relevance
“…Training of medical students is limited, as a survey of Canadian medical schools found that only 29% provided concussion-specific education while 43% incorporated concussion education into medical school curricula 76. A survey among Canadian medical residents identified a high rate of misperceptions about concussion outcomes (for instance, chronic traumatic encephalopathy, second impact syndrome) but, comparatively, residents were more knowledgeable than medical students due to having more experience in working with concussions 75…”
Section: Methodsmentioning
confidence: 99%
“…Training of medical students is limited, as a survey of Canadian medical schools found that only 29% provided concussion-specific education while 43% incorporated concussion education into medical school curricula 76. A survey among Canadian medical residents identified a high rate of misperceptions about concussion outcomes (for instance, chronic traumatic encephalopathy, second impact syndrome) but, comparatively, residents were more knowledgeable than medical students due to having more experience in working with concussions 75…”
Section: Methodsmentioning
confidence: 99%
“…[1] Recognition and diagnosis of concussion remains challenging due to the variability in clinical manifestations and symptoms, patient under-reporting, and a persistent lack of knowledge about this condition amongst participating athletes, parents, and even treating physicians. [2] [3] [4] In recent years, physician management of concussion has benefitted from the development of standardized concussion symptom inventories and computerized neuro-cognitive testing tools. [5] [6] [7] [8] None of these tools provide a window into the pathophysiology of concussion.…”
Section: Introductionmentioning
confidence: 99%
“…(27,28) However, another study from a medical school in the United States found more encouraging results, with 75% of respondents correctly defining concussion in a multiple-choice question format but significantly fewer being aware of its symptoms and management. (29) In the latter study, although nearly 40% of respondents had not received teaching on the subject, most were keen to learn more.…”
Section: Discussionmentioning
confidence: 99%